Pengembangan website koleksi langka Perpustakaan UGM sebagai preservasi digital heritage menuju era industri 4.0 - Maryono Maryono; Mardi Pramono (Universitas Padjadjaran, 2020)
Preserving rare collections is very important, considering the historical value in them, through digitalization and website development as the digital heritage preservation. The Google analytics data showed that the performance of UGM Library's rare collection website was still not significant, in terms of the number of users, visits, duration of visits, and repeat visits are still far from expectations. The purpose of this research was to find out the performance and use of the website, to find out the site that the user wants, and to formulate the development formula. The study used a combination of methods, through survey data collection with closed and open questionnaires plus interviews to deepen the problem: quantitative and qualitative analyses were performed, plus documentary analysis. The results showed that the website's performance was not yet encouraging; users wanted changes to 5 elements, namely appearance, visual appeal, information content, timely information, and ease of interaction. Expected developments include new historical nuances; installation of flipping book viewers and infographics; link addition; indexes, annotations, and recommended search; addition of reviews and social media columns. Google analytic data shows the need to reduce loading times by compressing PDF files and improving design according to mobile devices. Qualitative analysis succeeded in capturing the desire to access digital versions of Indonesian manuscripts in the Netherlands and the United Kingdom, and the need for additional graphic designer staff to improve the appearance and visual appeal.